INOVASI PENDIDIK DALAM BIDANG KETENAGAAN PENDIDIKAN - Rendi Pratama; Anugerah Helen Suhasri; Karoma Karoma; Mardiah Astuti (Cross-border, 2023)
This article aims to discuss innovation in the field of education and educational staff. The progress of the times and the challenges of today's increasingly rapid era, ideally educators and education staff must still learn, be creative in developing themselves with new discoveries in the world of education. Teaching and learning activities as a system, always get attention, both in the family, school, and society in general. Even so, teacher education graduates have not been able to fully improve the quality as aspired to. This is understandable because the problem of the quality of education is strongly influenced by many factors, including the quality of teachers, students, methods, tools, learning facilities and infrastructure, curriculum, costs, media, and environmental educational facilities. In the world of education, teachers have multi-role functions, namely as educators, instructors, and trainers. That is, the teacher as an educator refers to fostering and developing the affection of students, the teacher as a teacher refers to where the teacher conducts training and development of knowledge or intellectual brain teasers while the term teacher as a coach refers to the coaching and development of students' skills.